Challenges of International Social Work Research During the COVID-19 Pandemic: Lessons Learnt from A Bilateral Collaborative Study - Masateru Higashida; Amarawansa Ranaweera (Asian Social Work Journal, 2021)
The COVID-19 pandemic, which has had a profound impact on people’s lives around the world, has also affected international social work practice and research on social issues. This article explores how international social work research can draw lessons from bilateral research collaborations during the COVID-19 pandemic. In May 2021, an international collaborative research project was commenced to examine the practical experiences of social workers in Sri Lanka, with the overall purpose of contributing to development of socio-culturally relevant social work training. Trial semi-structured interviews were conducted using remote tools with five social workers in government or private organisations. The narratives of the interviewees were qualitatively analysed to identify their personal backgrounds of social work education and practice, their experiences of working during the pandemic and their perspectives and values as social workers. Lessons learnt were discussed focussing on the objectives and perspectives of the study, the preliminary arrangements for the research, the methods and considerations. In a context where it is important for social work researchers to promote international studies during and after the COVID-19 pandemic, this paper provides an example of a feasible international cooperative study.